How chrysanthemum (Chrysanthemum × grandiflorum) 'Palisade White' deals with long-term salt stress. Issue 3 (2nd April 2022) - Bandurska, Hanna; Breś, Włodzimierz; Tomczyk, Agnieszka; Zielezińska, Małgorzata; Borowiak, Klaudia
Abstract: Salinity is a serious problem in the cultivation of ornamental plants. Chrysanthemum ( Chrysanthemum × grandiflorum ) 'Palisade White' was evaluated in order to examine its responses to long-term salt stress. Plants were grown in substrate supplemented with NaCl doses (g dm −3 of substrate) 0, 0.44, 0.96, 1.47, 1.98, 2.48 and 2.99. The initial electrical conductivity (EC) of the substrates was 0.3, 0.9, 1.4, 1.9, 2.6, 3.1 and 3.9 dS m −1, respectively. Plant growth, relative water content (RWC), Na, Cl, K, N and P concentrations, membrane injury (MI), chlorophyll and proline levels, as well as gas exchange parameters in leaves of chrysanthemum were determined. A dose-dependent significant reduction of growth and minor decrease of leaf RWC were observed. Foliar Na and Cl concentrations increased with the highest NaCl dose up to 6-fold. However, the concentration of K increased by about 14 %, N by about 5 % but P decreased by about 23 %. Membrane injury was rather low (11 %) even at the highest NaCl dose. Statistically significant decreases of stomatal conductance (20 %), transpiration rate (32 %) and photosynthesis (25 %) were already observed at the lowest NaCl dose and about 40 % decrease of all these parameters with the highest dose. A significant reduction in the intercellular CO2 concentration occurred at the lower NaCl doses and no changes with the highest dose. These results show that in plants grown with the highest NaCl dose, non-stomatal limitation of photosynthesis may occur. According to Maas and Hoffman tolerance assessment (1977) chrysanthemum 'Palisade White' may be considered as moderately sensitive to salt stress in terms of growth inhibition. However, it is able to cope with long-term salt stress without any signs of damage, such as chlorophyll depletion, leaf browning or necrotic spots probably due to maintenance of K homeostasis and proline accumulation, which alleviate the toxic effect of chloride. Abstract : Plant species and cultivars vary in their sensitivity to salinity caused by sodium chloride. The aim of our study was the evaluation of the physiological and biochemical responses of Chrysanthemum × grandiflorum 'Palisade White' to the long-term salt stress. Salinity stress caused photosynthesis limitation and plant growth inhibition. Undisturbed potassium uptake and synthesis of amino acid proline probably help plants to deal with salt stress by protecting against its harmful effect. The research has shown that the examined chrysanthemum is moderately resistant to salt stress and is suitable for cultivation in slightly saline substrates.